Prevalence of chronic kidney disease by stage in diabetic patients - Irma Larios Jiménez; Enrique Villarreal Ríos; Liliana Galicia Rodríguez; Emma Rosa Vargas Daza; Lidia Martínez González (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
Fundamentals. Diabetes  mellitus  2  is  a  chronic  disease  with  an  increasing  prevalence  in  recent  years,  it  is  expected  that  by  2030  there  will  be  336  million  diabetics  worldwide,  and  the  increase  in  life expectancy  will  influence  the  presentation  of  chronic  complications,  including  chronic  kidney  disease with  a  prevalence  of  10  to  14%  of  the  adult  population.  The  objective  of  the  study  was  to  identify  the prevalence of chronic kidney disease by stage in diabetic patients Methods: A descriptive cross-sectional study in patients with a diagnosis of diabetes mellitus 2 included 426 patients attending the first level of care; were excluded patients with a diagnosis of diabetes mellitus 1, with rheumatic disease or with cystic nephropathy.  Sociodemographic  variables,  anthropometric,  serum  creatinine  and  glomerular filtration rates were studied according to the CKD-EPI formula. The analysis plan included averages, percentages,and confidence intervals. Results: Women  predominated  in  63.2%  (95%  CI;  58.6-67.8),  mean  age  62.99  years  (95%  CI;  61.99-63.99),  and  diabetes  evolution  time  11.89  years  (CI  95%;  11.16-12.62).  The  mean  glomerular  filtration rate was 81.34 ml/min (95% CI; 78.88-83.79), and stage 1 predominated with 46.6% (95% CI; 41.9-51.3). Conclusion:  The  prevalence  of  chronic  renal  disease  was  identified  by  stages  and  the  early  stages predominated.